2020
DOI: 10.3389/fphys.2019.01593
|View full text |Cite
|
Sign up to set email alerts
|

Induced Thermotolerance and Expression of Three Key Hsp Genes (Hsp70, Hsp21, and sHsp21) and Their Roles in the High Temperature Tolerance of Agasicles hygrophila

Abstract: Thermal adaptation plays a fundamental role in the expansion and distribution of insects, and heat shock proteins (Hsps) play important roles in the temperature adaptation of various organisms. To determine the roles of Hsp genes (Hsp70, Hsp21, and sHsp21) on the high temperature tolerance of Agasicles hygrophila, we obtained complete cDNA (complementary DNA) sequences for Hsp70, Hsp21, and sHsp21 by rapid amplification of cDNA ends (RACE), analyzed their expression profiles under different high temperature tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 58 publications
5
17
0
11
Order By: Relevance
“…Proteomic analysis performed in soybean roots supported our findings, where abundance of several heat shock proteins in response to flooding was found [ 62 ]. Studies have reported diverse roles of HSPs in regulating Rubisco activity under cold temperature stress in sunflower and barley and in chloroplast development even under abnormal growth conditions [ 63 , 64 , 65 , 66 , 67 ]. Under flooding stress, both light and carbon supplies are limited due to the slower diffusion rates in water, hence ATP synthesis is compromised, which causes carbohydrate starvation and disruption in mineral absorption and root hydraulic conductance [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis performed in soybean roots supported our findings, where abundance of several heat shock proteins in response to flooding was found [ 62 ]. Studies have reported diverse roles of HSPs in regulating Rubisco activity under cold temperature stress in sunflower and barley and in chloroplast development even under abnormal growth conditions [ 63 , 64 , 65 , 66 , 67 ]. Under flooding stress, both light and carbon supplies are limited due to the slower diffusion rates in water, hence ATP synthesis is compromised, which causes carbohydrate starvation and disruption in mineral absorption and root hydraulic conductance [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolated RNA was stored at −80 • C until first-strand cDNA synthesis was performed using a commercial reverse transcription kit (AT341-02, TransGen Biotech, China). Full-length cDNA of AhHsp70 and AhsHsp21 of A. hygrophila was produced by RT-PCR and rapid amplification of cDNA-ends (RACE)-PCR, and the resulting sequences were submitted to NCBI (GenBank accession numbers: MN138034 and MN163038, respectively, Supplementary Figures S2, S3; Jin et al, 2020a). We used A. hygrophila transcriptome data to obtain expressed sequence tags (ESTs) that showed similarities to other insect Hsfs.…”
Section: Rna Isolation Cdna Synthesis and Gene Cloningmentioning
confidence: 99%
“…The heat shock response was first described by Ritossa (1962) who observed an induction of specific chromosome puffs on the polytene chromosomes in Drosophila melanogaster following heat or chemical treatment; this constitutes an efficient defense system against detrimental effects of protein denaturation that are predominantly associated with heat stress. Subsequent studies elucidated the nature of induced RNAs and proteins at a molecular level and led to the isolation and characterization of Hsp genes (Lindquist, 1986;Lindquist and Craig, 1988;Nover, 1991;Lü et al, 2014;Deng et al, 2018;Jin et al, 2020a). Central to the heat shock response is the induction of Hsps that effectively counteract the effects of stress by stabilizing, re-folding, or degrading denatured proteins (Parsell and Lindquist, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 0 • C, the expression of GaHsp70-1 was 6-fold higher than that of GaHsp70-2. The importance of HSP70 in bacteria to eukarya has been demonstrated in numerous studies [50][51][52][53][54][55]. One study showed the abundance of HSP70 in the psychrophilic bacterium Shewanella frigidimarina when cells were exposed to heat stress at 28 • C [56].…”
Section: Discussionmentioning
confidence: 99%